STRATEGI CITRA BRANDING RUMAH SAKIT INTERNASIONAL NHS MELALUI KOMUNIKASI PEMASARAN TERPADU - Niken Sasadhara Sasmita; Santi Isnaini; Irfan Wahyudi (LPPM Stikosa - AWS, 2021)
This article results from research on the brand image strategy carried out by the National Hospital Surabaya (NHS) through integrated marketing communications. This study is on health services bases in the community currently entering the industrial and business era. The main problem arises in-hospital services, which have developed into an industry and are profit-oriented. This problem puts pressure on hospital managers and owners, especially on the cost dimension in private hospitals. Private hospitals must continue to improve management capabilities in carrying out hospital operations with good quality standards to the best compared to other hospitals. The research uses a case study research method with a qualitative approach. Data collection and analysis techniques use observation and in-depth interviews so that they can be analyzed exploratively. The results of this study are the first are there are many reasons why the marketing department of NHS adopts Integrated Marketing Communication (IMC) in their sales strategy. It also happens in the healthcare industry, namely hospitals. One of the reasons that become the basis is that marketers understand and recognize strategies integrating into various communication functions rather than running these communication functions alone. Second, marketing communication theory becomes the rationale for processing data and analyzing the phenomenon of problems regarding strategic concepts in policy determination to the direction of marketing communication strategies carried out by NHS hospitals. This research concludes that the main problem arises in hospital services, which have developed into an industry and are profit-oriented. Strategic management skills will become more critical as pressure increases to find future revenue and growth opportunities. These opportunities will come through various combinations of new healthcare products and services, increasing penetration into high-priority market segments, or accessing new markets that are not serving currently.